Grotesque Character as A Criticism to Racism in Flannery O' Connor's "The Geranium" (NOBEL: Journal of Literature and Language Teaching, 2020)
Grotesque character commonly refers to Southern Black or Black character who represents “misfit” and “freak” and bad things. Grotesque character is often used in Flannery O’Connor’s short stories to criticize the issues in society. In the short story “The Geranium,” she criticizes the Black racial issue in White society at that time. This paper aims at showing how a White character, Old Dudley, who is considered as having high status, is placed as a grotesque character in the form of a “freak” person with dislocations and hallucination. This paper also intends to show how O’Connor represents Southern, and Northern Black characters legitimated as grotesque or evil in White society indeed have good sides. This study finds out that grotesque is used to address a criticism toward White supremacy on Black subordination and that grotesque is indeed a bad part of the dual quality (good and bad) of all human characters in the short story.